Late Jurassic multituberculate mammals from Langenberg Quarry (Lower Saxony, Germany) and palaeobiogeography of European Jurassic multituberculates. (4th May 2021) - Martin, Thomas; O. Averianov, Alexander; A. Schultz, Julia; H. Schwermann, Achim; Wings, Oliver
ABSTRACT: The Late Jurassic (late Kimmeridgian) multituberculate assemblage from the Langenberg Quarry in Northern Germany includes Paulchoffatiidae indet., the pinheirodontid Teutonodon langenbergensis, and Cimbriodon multituberculatus gen. et sp. nov. of the paulchoffatiid line. A fragmentary m1 that was formerly attributed to Eobaataridae indet. is now assigned to the paulchoffatiid line. Teutonodon langenbergensis is one of the largest known Jurassic multituberculates and most derived known member of Pinheirodontidae. Cimbriodon multituberculatus, a derived member of the paulchoffatiid line is characterised by the upper premolars P4 and P5 showing three rows of cusps, with P5 having numerous cusps and being distinctly longer than P4, and the lower premolars p3 and p4 showing five serrations with long ridges. The new taxon is unique among multituberculates by the presence of several lingual cusps on p3 and p4. Rugosodon from the Late Jurassic of China differs from Paulchoffatiidae or Pinheirodontidae by seven serrations on p4, significantly reduced buccal cusps on p4, a p3 that has half the length of p4, and a simple bicuspid I3, and is referred to the paulchoffatiid line. Allodontidae is known only from western North America, Paulchoffatiidae and Pinheirodontidae only from Western and Central Europe (Portugal, Spain, Great Britain, and Germany). Plagiaulacidae is known from the earliest Cretaceous of Great Britain and of western North America. Zoobank: urn:lsid:zoobank.org:pub:D8ECDD1D-931D-47E3-AAEE-D421B4C7079D